Becoming American, being Indian : an immigrant community in New York City - Khandelwal, Madhulika S. (Madhulika Shankar), 1957- (Anthropology of contemporary issues., 2002)
Since the 1960s the number of Indian immigrants and their descendants living in the United States has grown dramatically. Madhulika S. Khandelwal explores the ways in which their world has evolved over four decades.